PRELIMINARY INVESTIGATION ON THE POSSIBLE CAUSATIVE AGENT OF EPIZOOTIC ULCERATIVE SYNDROME IN FISHES OF WEST BENGAL - Mandal, A K; Nandi, N C; Sarkar, N C; Mandal, F B (Indian Journal of Fisheries, 2011)
The presence of bacteria and a flagellated protozoan, Costia necatrix Henneguy has been reported inassociation with Epizootic Ulcerative Syndrome (EUS) in fishes of West Bengal.